Grandiosity, vulnerability, and narcissistic fluctuation: Examining reliability, measurement invariance, and construct validity of four brief narcissism measures - Henttonen, Pentti; Salmi, Juha; Peräkylä, Anssi; Krusemark, Elizabeth A. (Frontiers in Psychology, 2022)
Continued interest in the distinction between grandiose narcissism, vulnerable narcissism and the fluctuation between grandiose and vulnerable states has expanded the repertoire of self-report instruments. The present study examined the psychometric properties of four brief narcissism measures (the Narcissistic Personality Inventory-13 (NPI-13), Hypersensitive Narcissism Scale (HSNS), Super-Brief Pathological Narcissism Inventory (SB-PNI), and the g-FLUX) in a Finnish sample of university students. Confirmatory factor analyses supported the reliability of the NPI-13, g-FLUX, SB-PNI Vulnerability, and two HSNS subfactors (Oversensitivity and Egocentrism). Tests of measurement invariance indicated the NPI-13, SB-PNI Vulnerability, HSNS Oversensitivity, and the g-FLUX perform similarly between males and females and are generally similar between individuals in younger and older age groups. Construct and predictive validity were evaluated by examining relations between narcissism measures and relevant criteria including psychopathology symptoms, self-esteem, well-being, five factor traits, and empathy. Results supported the construct validity of all four measures, while correlational profiles highlighted the convergence between the g-FLUX and measures of both grandiosity and vulnerability. The NPI-13 was most predictive of NPD symptoms, whereas vulnerable narcissism measures were most predictive of psychopathology. Results further establish the psychometric properties of the NPI-13, SB-PNI Vulnerability, HSNS Oversensitivity, Egocentrism, and provide new validation of the g-FLUX.